Pth Moment Exponential Stability of Switched Discrete-Time Stochastic Systems: A Multiple Lyapunov Functions Method. Issue 13 (September 2021) - Fan, Lina; Zhu, Quanxin
Abstract: This paper studies the p th moment exponential stability of switched discrete-time stochastic systems with stable and unstable subsystems. By using multiple Lyapunov functions and mode-dependent average dwell time, we provide a sufficient condition for the p th moment exponential stability with fast convergence rate for deterministic switched discrete-time stochastic systems with stable and unstable subsystems. Obviously, our result has a weaker conservatism than those previous results where the effect of random factor was ignored. In addition, the criteria for stability and instability of discrete-time stochastic systems without switching are provided. Finally, the correctness of the results is verified by two numerical examples. To the best of our knowledge, it is the first time that the stability of discrete time switching system with random disturbance has been discussed.